Gut microbiota–mitochondrial inter-talk in non-alcoholic fatty liver disease - Zhang, Qi; Xing, Wenmin; Wang, Qiao; Tang, Zhan; Wang, Yazhen; Gao, Wenyan (Frontiers in Nutrition, 2022)
The increasing prevalence of nonalcoholic fatty liver disease (NAFLD), which is a progressive disease, has exerted huge a healthcare burden worldwide. New investigations have suggested that the gut microbiota closely participates in the progression of NAFLD through the gut-liver axis or gut-brain-liver axis. The composition of the microbiota can be altered by multiple factors, primarily dietary style, nutritional supplements, or exercise. Recent evidence has revealed that gut microbiota is involved in mitochondrial biogenesis and energy metabolism in the liver by regulating crucial transcription factors, enzymes, or genes. Moreover, microbiota metabolites can also affect mitochondrial oxidative stress function and swallow formation, subsequently controlling the inﬂammatory response and regulating the levels of inﬂammatory cytokines, which are the predominant regulators of NAFLD. This review focuses on the changes in the composition of the gut microbiota and metabolites as well as the cross-talk between gut microbiota and mitochondrial function. We thus aim to comprehensively explore the potential mechanisms of gut microbiota in NAFLD and potential therapeutic strategies targeting NAFLD management.